(untitled) (Research, Society and Development, 2024)
Spinal anesthesia, also known as neuraxial block, is widely used as an anesthetic method in pregnant women, especially during cesarean sections. This procedure involves the application of a local anesthetic in the subarachnoid space, between the L3-L4 vertebrae, based on the palpation of the patient’s anatomical landmarks. During pregnancy, the woman’s body undergoes several significant changes, with weight gain being one of the most evident. This weight gain is even more pronounced in obese pregnant women, who have a body mass index (BMI) greater than 30 kg/m². In obese patients, anatomical landmarks are often hidden due to the accumulation of adipose tissue, making spinal anesthesia more difficult to perform. Given the complexity of this scenario, there is a need for auxiliary methods that can ensure the precision of the anesthetic procedure. Lumbar ultrasound has emerged as an effective tool in this regard, allowing clearer and more precise visualization of anatomical landmarks. This article aims to explore the benefits of pre-procedural ultrasound in spinal anesthesia for obese pregnant women, proposing a solution to the difficulties encountered and demonstrating, based on published studies, how this technology can improve the safety and efficacy of neuraxial block.